Fuel Optimization Using Potassium Permanganate (KMnO4) on Biodiesel and Diesel Blend as an Additive - Sutcu, Deniz; Aydin, Selman; Celebi, Yahya; Aydin, Ahmet (Wiley, 2025)
This study explores the influence of potassium permanganate (KMnO4) as an additive in biodiesel-diesel mixture on the combustion, performance, and emissions characteristics of a diesel engine. Three fuel blends were prepared and tested: pure diesel, 12% waste vegetable biodiesel, 88% diesel (B12), and 12% waste vegetable biodiesel, 88% diesel with KMnO4 additive (PMB12). Experiments were conducted on single-cylinder, water-cooled, four-stroke diesel engine at 1500 rpm and various load conditions. Results showed that the addition of KMnO4 enhanced the physicochemical features of the biodiesel-diesel blend. PMB12 exhibited the highest in-cylinder pressure at low and medium loads while heat release rate values were found to be the lowest. It also demonstrated shorter ignition delay and higher mean gas temperature. Adding KMnO4 deteriorated brake-specific fuel consumption up to 16% compared to diesel. Brake thermal efficiency of the blend with KMnO4 showed a good performance, obtaining the same value with diesel at low and medium, while it was decreased by 8.6% for PMB12 at high load. Emission analysis revealed that carbon dioxide emissions increased with load but remained relatively stable across the test fuels. Nitrogen oxides were obtained higher up to 14%. Hydrocarbon emissions were varied with load, with B12 and PMB12 showing higher emissions at low and high operations.
Keywords: biodiesel; combustion; diesel engine; emissions; KMnO4 additive